Focus on the Family: Juvenile Court Responses to Girls and Their Caretakers. (October 2014) - Morash, Merry; Stevens, Tia; Yingling, Julie
Interviews with 27 girls and the professionals who worked with them yielded retrospective accounts of court interventions into families. Contradicting prior criticisms, for the setting and sample, girls were not confined to control sexual activity or as punishment for crimes committed after they ran from abusive families. Intervention problems included holding girls responsible for fighting with physically abusive caretakers, and electronically forced presence in homes with destructive caretakers. Family counseling benefitted girls with troubled families. Independent living benefited those with intractably destructive families. The research generated contemporary local information about broad criticisms leveled against juvenile courts' responses to girls.